Task-Irrelevant Novel Sounds Improve Attentional Performance in Children With and Without ADHD - Tegelbeckers, Jana; Schares, Laura; Lederer, Annette; Bonath, Bjoern; Flechtner, Hans-Henning; Krauel, Kerstin (Frontiers in Psychology, 2016)
Task-irrelevant salient stimuli involuntarily capture attention and can lead to distraction from an ongoing task, especially in children with ADHD. However, there has been tentative evidence that the presentation of novel sounds can have beneficial effects on cognitive performance. In the present study, we aimed to investigate the influence of novel sounds compared to no sound and a repeatedly presented standard sound on attentional performance in children and adolescents with and without ADHD. We therefore had 32 patients with ADHD and 32 typically developing children and adolescents (8 to 13 years) executed a flanker task in which each trial was preceded either by a repeatedly presented standard sound (33%), an unrepeated novel sound (33%) or no auditory stimulation (33%). Task-irrelevant novel sounds facilitated attentional performance similarly in children with and without ADHD, as indicated by reduced omission error rates, reaction times, and reaction time variability without compromising performance accuracy. By contrast, standard sounds, while also reducing omission error rates and reaction times, led to increased commission error rates. Therefore, the beneficial effect of novel sounds exceeds cueing of the target display by potentially increased alerting and/or enhanced behavioral control.